The Politics of Educational Reform in Ghana Understanding Structural Persistence in the Secondary School System - Aziabah, Maxwell A. (Critical Studies of Education ;, 2018)
This book comprises five main chapters and addresses the core research question: How can the endurance of academic bias in Ghana's secondary education system be explained in the context of educational reform versus change of government concurrence? Six sub-questions have subsequently been derived from the core research question, enabling a comprehensive and rigorous treatment of the subject matter of investigation. The manuscript adopts an historical institutionalism approach, combining path dependency with partisan theory in explicating structural persistence in the secondary school system in Ghana. A case study methodological design procedure has been employed in the investigation of three episodes of educational reform, anchored on qualitative content analysis as the main data reduction mechanism. .